(3aJhI fhM Ydjg GdSdGes - (3eMeO Hf Ydj GdQVjs
(3ChdgG (B:s
(3CeG HYO abO Qhi Yf eMeO Hf GdSjO Ydi Hf GdQGVi Yai Yfg eUfa gPg GdaJhg s
(3BNQgG (B:s
(3hdgPG cGf HSdjeGf hEPG cGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs